Contribution of Small Scale Photographs in Forest Resources Survey of East-godavari - Seth, V. K.; Tomar, M. S. (Indian Forester, 1973)
Small scale photographs on 1:60,000 scale have been used for forest resources survey over 10,416 sq km in East-Godavari, Andhra Pradesh during the year 1970. The photographs were used for location of sample plots on ground, eliminating non-forested plots from ground cruising, area estimates of different landuse and forest cover types and locating them on one-inch maps. The various landuse and forest cover types interpreted on aerial photographs are (1) agriculture including habitation, (2) water surface, (3) blanks and grasslands, (4) shifting cultivation, and (5) forest land. The forest land was further stratified in (a) high volume, (b) medium volume, (c) low volume and (d) plantations. The three volume strata were further sub-classified into five crown density classes of 20%. Suitable plantation sites were also interpreted. The main contribution of photo interpretation lies in making error in area estimation very small. Estimation of stratum area from ground data alone is subject to high sampling error. Therefore, estimation of total volume by strata, taking area information from photo and volume/ ha from ground plots, results in significant gains in precision. This is in addition to the landuse and forest cover types maps which are obtainable from aerial photo-interpretation as by-product. The cost of photography, photo-interpretation, area calculation and mapping (excluding the cost of ground sampling) came to Rs. 8.00 sq km.